Granulomatous prostatitis mimicking prostate cancer in a patient with psoriatic arthritis: a case report - Luigi De Luca; Felice Crocetto; Biagio Barone; Massimiliano Creta; Salvatore Pesce; Achille Aveta; Maria Raffaela Campanino; Ciro Imbimbo; Nicola Longo (Future Science OA)
Granulomatous prostatitis (GP) is an unusual and benign inflammatory condition of the prostate, where autoimmunity has been recognized as a key factor in the pathogenesis of GP in a subset of patients. Clinically, GP poses diagnostic challenges as it may strongly mimic prostate cancer from a clinical, biochemical and radiological point of view. The occurrence of GP in patients suffering from psoriasis, a systemic autoimmune disease, has never been investigated. We describe the case of GP in a patient with psoriatic arthritis presenting with an increased prostate specific antigen level, and evidence of a nodular lesion visualized by prostate multiparametric magnetic resonance imaging, which was highly suspicious for aggressive prostate cancer.